Information On Pharmacy Inventory Management With Forecasting Method (Double Moving Average & Double Exponential Smoothing) - Christofer Christofer (Komunitas Dosen Indonesia, 2021)
Inventory on Pharmacy often experiences stockpiling of goods so that it wastes more costs and the manual process of recording goods using excel. Double Moving Average dan Double Exponential Smoothing Method With a program that uses the forecasting method, it can assist in managing the stock of goods that will be needed in the following month, with this system, the pharmacy owner can view stock and manage sales data and find out computerized sales income and shop owner can save cost in stock items